Fatigue life analysis of the radial cylindrical roller bearings: roller end-flange construction effect - Bayrak, Ramazan; Sagirli, Ahmet (TAYLOR & FRANCIS INC, 2023)
The fatigue life analysis of radial Cylindrical Roller Bearings (CRBs) is performed by considering the effects of the roller end-flange construction. A NUP-type CRB with the conical flange and the rollers having spherical ends is considered under various combined loads. The effect of the variation of the flange angle on the bearing life is addressed. The slicing method is employed to obtain bearing internal load distribution, and the elastic half-space method is used to calculate contact pressures and subsurface stresses, which are necessary for bearing life calculations. For the combination of radial and axial loading, it's observed that the bearing life decreases up to a certain value of the flange angle, and the changes in the life are minimal after a certain flange angle. For high misalignment angles of the inner ring with radial loading, the results show that the predicted life decreases until a particular flange angle and then increases with increasing flange angle. The change in the bearing life depending on the flange angle is mainly attributed to the change in the roller tilt angle versus the flange angle.
Keywords: Cylindrical roller bearing; flange angle; fatigue life; contact pressure; subsurface stress; INTERNAL CLEARANCE; LOAD DISTRIBUTION; EHL ANALYSIS; HIGH-SPEED; CONTACT; PREDICTION; BALL; MISALIGNMENT; STRESSES; FRICTION; Mechanics